High Valging Tibial Osteotomy in the Complex Treatment of Anterior Cruciate ligament Ruptures in Patients With Varus Gonarthrosis of the Knee - V. V. Zayats (Неотложная медицинская помощь)
MATERIALS AND METHODS. We observed 164 patients from 2013 to 2019 (mean age 39.8 ± 5.1 years) who underwent anatomical antegrade ACLR ВТВ autograft . Group 1 (43 people, 31.1%) and Group 2 (48 patients, 29.3%) included patients with isolated medial GA of 2-3 degree and/or varus deformity of at least 5º. Group 3 (73 people or 44.5%) included patients with normal articular cartilage and the correct axis of the limb. In Group 1, ACLR was supplemented with an “open wedge” HVTO. The assessment was carried out according to Lysholm Knee Scoring Scale, 2000 IKDC, KOOS.RESULTS. The simultaneous performance of HVTO and ACLR shows good clinical and radiological results in 93% in the first year, and three years after surgery keeps it in 88.4%. The results of treatment of patients of Group 1 turned out to be significantly better in comparison with Group 2 (p<0.01). In Group 1, the anteroposterior and rotational hypermobility of the knee joint was 16.3%, less commonly we observed pain, synovitis, atrophy of the muscles of the thigh and contracture (p <0.01), some dysfunctions (C according 2000 IKDC scale) were determined in 11.6% (p<0.05), and significant impairment of the knee joint function (D according to 2000 IKDC scale) were not observed (p<0.001). In the first 5 years after surgery, a much larger number of patients of the 1st group were able to fully return to their work, domestic and sports activities, compared with Group 2 (p<0.05).CONCLUSION. The combined ACLR and HVTO allow reliable technology in the treatment of anterior instability in patients with GA (p< 0.05%). This approach is effective in young active middle-aged patients, with anterior instability of the knee joint and varus GA or prerequisites for its development, as well as with revision ACLR, posterior tibial plateau tilt of more than 12º. Performing HVTO simultaneously with ACLR is not practical for patients with valgus deviation of the lower leg, failure of the posterolateral capsular ligamentous complex, or changes in the external joint.